New Glossopterid Polysperms from the Permian La Golondrina formation (Santa Cruz province, Argentina): potential affinities and biostratigraphic implications - Cariglino, Barbara (2015)
Impression fossils of ovuliferous fructifi cations from the Permian La Golondrina Formation in Santa Cruz, Argentina, are described, their affi nities compared, and fi nally, assigned to the Arberiaceae (Glossopteridales). Based on morphological differences from the genera in Arberiaceae, a new taxon is established for some specimens, whereas others are allocated to Arberia madagascariensis (Appert) Anderson & Anderson. This is the fi rst record of Arberiaceae from the La Golondrina Basin. The biostratigraphic implications of the occurrence of this family in this unit are discussed, and suggest that more evidence other than that provided by the megafl oral elements is needed to resolve the age of the constituent members of the La Golondrina Formation.